Pengaruh Budaya Organisasi, Motivasi, dan Komitmen Organisasi Terhadap Kinerja Pegawai - Ariyanto Ariyanto; Maat Pono; Abdul Razak Munir (Magister Management, Hasanuddin University, 2019)
The big challenges faced by the government today is to perform effectively and efficiently. The purpose of the study was to analyze the influence of organizational culture, motivation, and organizational commitment on employee performance in the case of education office province in South Sulawesi. The sample used was 138 respondents. Data obtained through questionnaire distribution to the government employees assigned in the education office of the South Sulawesi Province. The method used is path analysis that is run with the SPSS 25 for Windows program. The results showed that organizational culture had a positive and significant effect on employee performance, motivation had a positive and significant effect on employee performance, and organizational commitment had a positive and significant effect on employee performance.